Instructional Communication Scholarship: Complementing Communication Pedagogy - Alan K. Goodboy (Central States Communication Association, 2018)
Instructional communication and communication pedagogy are complementary areas of inquiry; that is, communication instructors will not be effective educators without strategically considering--for each course taught in a given semester--both pedagogical techniques (e.g., writing accurate course objectives; choosing or creating activities that align with the objectives; teaching communication skills using proven pedagogical strategies) and instructional communication practices (e.g., communicating with students clearly; confirming students; integrating appropriate humor). These disciplines offer micro (i.e., communication pedagogy) and macro (i.e., instructional communication) perspectives on teaching that both deserve close attention as instructors strive to be the best educators (and communicators) in the communication courses that they teach.